Adverse neural effects of delayed, intermittent treatment with rEPO after asphyxia in preterm fetal sheep. (18th June 2021) - Dhillon, Simerdeep K.; Wassink, Guido; Lear, Christopher A.; Davidson, Joanne O.; Gunn, Alistair J.; Bennet, Laura
Abstract : Key points: We have previously shown that high‐dose constant infusion of recombinant human erythropoietin (rEPO) from 30 min to 72 h after asphyxia in preterm fetal sheep reduced histological injury and improved electrophysiological recovery. This study shows that a high‐dose infusion of rEPO from 6 to 72 h after asphyxia did not improve EEG recovery, oligodendrocyte and neuronal survival at 1 week post‐asphyxia. Of concern, intermittent rEPO boluses started 6 h after asphyxia were associated with impaired EEG recovery and bilateral cystic injury of temporal lobe intragyral white matter. Intermittent boluses of rEPO were associated with significantly increased cerebral vascular resistance and hypoperfusion, particularly after the first dose, but did not affect seizures, suggesting mismatch between perfusion and brain activity. Abstract: Recombinant human erythropoietin (rEPO) is a promising treatment for hypoxic‐ischaemic brain injury. Disappointingly, a large randomized controlled trial in preterm infants found that prophylactic, repeated high‐dose rEPO boluses started within 24 h of birth did not improve neurodevelopmental outcomes. We examined whether initiation of a continuous infusion of rEPO at the end of the latent phase after hypoxic‐ischaemia (HI) might improve outcomes compared with intermittent bolus injections. Chronically instrumented preterm (0.7 gestation) fetal sheep received sham asphyxia or asphyxia induced by complete umbilical cord occlusion for 25 min. Six hours after asphyxia, fetuses received either a continuous infusion of rEPO (loading dose 2000 IU, infusion at 520 IU/h) from 6 to 72 h post‐asphyxia or intravenous saline or 5000 IU rEPO, with repeated doses every 48 h for 5 days. Continuous infusion of rEPO did not improve EEG recovery, oligodendrocyte and neuronal survival at 1 week post‐asphyxia. By contrast, intermittent rEPO boluses were associated with impaired EEG recovery and bilateral cystic injury of temporal lobe intragyral white matter in 6/8 fetuses. These studies demonstrate for the first time that initiation of intermittent rEPO boluses 6 h after HI, at a dose comparable with recent clinical trials, exacerbated neural injury. These data reinforce the importance of early initiation of many potential neuroprotective therapies. Key points: We have previously shown that high‐dose constant infusion of recombinant human erythropoietin (rEPO) from 30 min to 72 h after asphyxia in preterm fetal sheep reduced histological injury and improved electrophysiological recovery. This study shows that a high‐dose infusion of rEPO from 6 to 72 h after asphyxia did not improve EEG recovery, oligodendrocyte and neuronal survival at 1 week post‐asphyxia. Of concern, intermittent rEPO boluses started 6 h after asphyxia were associated with impaired EEG recovery and bilateral cystic injury of temporal lobe intragyral white matter. Intermittent boluses of rEPO were associated with significantly increased cerebral vascular resistance and hypoperfusion, particularly after the first dose, but did not affect seizures, suggesting mismatch between perfusion and brain activity.